P3-S7.16 Lactobacillus crispatus colonisation reduces risk of Bacterial Vaginosis (BV) acquisition. (10th July 2011) - Antonio, M; Petrina, M; Meyn, L; Hillier, S
Abstract : Background: Longitudinal studies have found that vaginal colonisation by hydrogen peroxide-producing strains of lactobacilli is associated with a reduced risk of BV acquisition. Several Lactobacillus spp. including L crispatus, L jensenii, and L gasseri can produce hydrogen peroxide, but no longitudinal studies to date have assessed whether all hydrogen peroxide producing species are equally protective. The objective of this study was to determine which species of Lactobacillus were associated with a reduced risk of BV acquisition. Methods: In this secondary analysis of women enrolled in a vaccine trial, 112 women aged 18–40 who had Gram stain Nugent scores <6 at study entry were followed bimonthly for up to 18 months for acquisition of BV. Vaginal and rectal swabs were collected at each visit for culture identification of lactobacilli. Species identification was performed by repetitive sequence PCR, and if necessary, 16S rRNA gene RFLP or sequencing. Cox proportional hazards models were used to assess the association between Lactobacillus colonisation at the prior visit and BV acquisition. Results: There were 40 BV acquisitions detected during 486 follow-up visits over 65.3 woman-years for an incidence of 61 per 100 woman-years. As shown in Abstract P3-S7.16 table 1, women colonised by L crispatus were 53% less likely to acquire BV at a subsequent visit (p=0.023). Conclusions: L crispatus was the only species protective against BV acquisition. Since neither L jensenii nor L gasseri reduced the risk of BV despite their capacity to produce hydrogen peroxide, other characteristics of L crispatus may be more critical then peroxide production in protecting from BV acquisition.